An analysis of effectiveness of individual competences in strategic leadership among principals of excellent secondary schools Malaysia - Salleh, Mohamad Johdi; Mohamad, Nazifah Alwani (Journal of Creative Writing, 2015)
The study examines the effectiveness of individual competences in strategic leadership among principals of excellent secondary schools Malaysia. The study used the purposive sampling in order to select the secondary schools in Selangor which have demonstrated excellent performance in academic achievement particularly in the Lower Secondary Assessment or Penilaian Menengah Rendah (PMR) from 2008 to 2010. The respondents involved 175 school leaders including the principals, senior assistants, coordinators and heads of departments. Questionnaires have been used as a research instrument for the data collection purpose which was developed and assessed by Davies and Davies (2005). The analysis of the result shows that the component of restlessness is the most effective practice with the highest mean score of 4.5278 and standard deviation of 0.44633. This is followed by the component of adaptive capacity with a mean score of 4.4167 and standard deviation of 0.48714. The third most effective practice is represented by the component of absorptive capacity with a mean score of 4.3981 and standard deviation of 0.49002. On the other hand, the principals have identified the component of wisdom as the least effective practice of individual characteristics with mean score of 4.3667 and standard deviation of 0.46965. It is hoped that this study would effectively benefit leaders and educators in schools towards in realizing the Malaysian Education Development Plan 2013-2025, and, teacher professional development all over the world.